Comparative efficacy and toxicity of immune checkpoint inhibitors in combination with or without chemotherapy treatment for advanced esophageal squamous cell carcinoma: A systematic review and meta-analysis - Ma, Yue; Xin, Yu; Su, Dan; Zhou, Yuxin; Li, Hongxu; Zou, Haoyi; Yu, Xuefan; Yang, Qing; Cui, Jie; Wang, Changsong; Zhang, Yanqiao (Frontiers in Oncology, 2022)
We did a systematic review and meta-analysis to assess the efficacy and safety of Immune checkpoint inhibitors combined with or without chemotherapies in patients with esophageal squamous cell carcinoma. Related to the treatment of esophageal squamous cell carcinoma with Immune checkpoint inhibitors therapy was retrieved from the database construction to August, 2022. The risk of bias was assessed using the Cochrane Manual standard and RevMan 5.3 software for data synthesis. The outcome measures observed included overall survival, 12-month survival, disease control rate, objective response rate, treatment-related adverse events of grade 3 or higher, and progression-free survival. The adverse reactions included fatigue, diarrhea, hypothyroidism, rash, anemia, and anorexia. In this meta-analysis, a total of 17 randomized controlled trials were included. In first-line therapy, Immune checkpoint inhibitors combined with or without chemotherapy in the treatment of esophageal squamous cell carcinoma was more effective than chemotherapy alone. Overall survival, 12-month survival rate, and objective response rate were statistically significant. Among second-line treatments, Immune checkpoint inhibitors combined with or without chemotherapy in the treatment of esophageal squamous cell carcinoma had statistically significant overall survival, 12-month survival, objective response rate, treatment-related adverse events of grade 3 or higher, and progression-free survival compared with chemotherapy alone. Both first-line and second-line immune checkpoint inhibitors is effective for esophageal squamous cell carcinoma, and the adverse reactions are controllable and safe.